Faktor Yang Mempengaruhi Penegakan Hukum Tindak Pidana Korupsi Pada Tingkat Banding Di Pengadilan Tinggi Palembang - Isisu, Septika Intan; Hayatuddin, Khalisah; Mahfuz, Abdul Latif (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This paper describes the high court as one of the pillars of law enforcement, including law enforcement against corruption, which rarely gets attention in scientific works or research. The research method used is juridical and empirical research methods. This can be seen from the lack of discussion in scientific works and research related to appeal cases in court at the High Court. The formulation of the problem to be studied is what are the factors that influence law enforcement against corruption at the Appeal Level at the Palembang High Court. Based on the results of the research and discussion of the subject matter, it can be concluded that the factors that influence law enforcement against corruption at the Appeal Level at the Palembang High Court include: legal factors, such as the authority of the panel of judges at PT in deciding cases only 3 or 4 times the trial only, referring to SEMA No. 2 of 2014 that the decision of the panel of judges may not last more than 3 months; Law enforcement factors, such as the workload of Judges at the Palembang High Court are quite heavy, even during a pandemic they have to resolve an average of 300 cases in one year; Facility factors, such as office facilities, courtrooms, means of communication and others; Community factors, such as opinions that develop in society which are usually expressed through the mass media; Cultural factors, such as being attached to the rule of law and the rule of ethics, sometimes make the profession of a judge a lonely profession, being on top of an ivory tower, and even having a house on the wind.